Dukungan Yang Dibutuhkan Dalam Implementasi Jabatan Fungsional Penilai Pemerintah Di Lingkungan Pemerintah Daerah Berdasar Pendekatan Analisis USG - Fitriana Januar Arifiana; Ibung Prasetiya Utama; Jundi Widiantoro (Ridwan Institute, 2022)
As a servant of government affairs, ASN is responsible for the development and implementation of strategic policies to maintain the continuity of government programs. The purpose of this study is to show what forms of support are needed by PFPP on the part of the state government in carrying out the evaluation function in the current conditions, and the most urgent, most serious, and most extensive support assistance. if this is not immediately addressed, placement will be made immediately and alternative solutions will be sought to support the effectiveness of the State Assessor's operational duties and duties in the current conditions. Data collection in research activities is a technique that is processed to obtain the necessary data and data sources, which can then be used with analytical techniques to draw sufficient conclusions, so that the method of data collection must be regulated appropriately. These results are the formulation of the problem as the most important and urgent risk management method in the administration of regional governance from the JFPP point of view, so that this information can serve as an example for the Ministry of Administrative and Bureaucratic Reform. , Ministry of Home Affairs or Ministry of Finance. As an oversight authority, DJKN determines the preferred political direction, especially to support the efficiency of carrying out tasks related to the duties of state experts. In conclusion, JFPP needs some form of local government support that is considered urgent and serious, which has the potential to worsen if not addressed immediately.